Bivariate multilevel modeling of antenatal care contacts and place of delivery among reproductive-aged women in Ethiopia - Denekew Bitew Belay; Seniat Mulat; Nigussie Adam Birhan; Ding-Geng Chen (PLoS ONE, 2025)
Background Antenatal care (ANC) contacts, along with enhanced health facilities for delivery, are essential components of maternal and child healthcare, as these significantly contribute to both mothers and their newborn child’s health. Antennal care contacts primarily help women maintain normal pregnancies by detecting pre-existing conditions and preventing complications that may arise during childbirth. This study intended to determine possible factors that affect both ANC contact and place of delivery among women in Ethiopia. Methods The 2019 Ethiopian Mini Demographic and Health Survey data were used for this study. A total weighted sample of 3,926 women nested within 68 zones was used. The bivariate multilevel logistic regression model was utilized to assess the association between antenatal care contact and place of delivery and determinant factors among reproductive-aged women in Ethiopia. Results In this study, 57% and 47.5% of women had no ANC contacts and home delivery respectively. Similarly, about 36.73% of women delivered at home and didn’t utilize the recommended ANC contacts. Only 32.99% of women have both health facility delivery and at least four ANC contacts during their pregnancy. Women who reside in rural areas were 0.612 and 0.352 times less likely to have ANC and health facility delivery compared to women who reside in urban areas. Whereas, the estimated odds of women with higher education levels were 3.803 and 8.406 times the estimated odds of women with no education. Conclusion A high proportion of women are still delivering their new child at home and still don’t have at least four ANC contacts during their pregnancy. Women’s age, women education level, marital status, wealth status, sex of household head, place of residence, and region were significant predictors of antenatal care visits and place of delivery simultaneously in Ethiopia. Although the country tried to maximize these services, it still requires expansion of health facilities media campaigns, and women’s literacy to reduce maternal and newborn child mortality in Ethiopia.